Habitat segregation and rare hybridization between Gasterosteus aculeatus and Gasterosteus nipponicus around the Sea of Okhotsk and the Bering Sea - Yu Endo; Atsushi J. Nagano; Dmitry Lajus; Yo Y. Yamasaki; Jun Kitano (Ichthyological Research, 2026)
Understanding how genetic differentiation is maintained between closely related species with overlapping habitats is a central question in evolutionary biology. The sticklebacks Gasterosteus aculeatus and Gasterosteus nipponicus occur in sympatry with reproductive isolation on the Pacific coast of Hokkaido Island. However, their distributions and hybridization patterns in more northern regions remain largely elusive. Here, we analyzed species distributions and hybrid occurrences in Sakhalin, the Northern Territories, the Kuril Islands, the Pacific and Okhotsk coasts of Kamchatka, Chukotka, and the open Bering Sea using genome-wide nucleotide variant data. We found that G. nipponicus is largely restricted to Sakhalin, while G. aculeatus predominates in other regions, with only rare hybrids detected. These findings indicate largely allopatric distributions around the Sea of Okhotsk and the Bering Sea. These allopatric populations provide valuable opportunities for comparing patterns of genetic differentiation and phenotypic divergence between allopatric and sympatric species pairs.

Divergent developmental trajectories of body depth and head length among stickleback populations - Hiyu Kanbe; Seiichi Mori; Jun Kitano (Ichthyological Research, 2026)

Shared and Unique Patterns of Genomic Differentiation and Introgression Between Japanese Stickleback Species Across Three Sympatric Sites - Genta Okude; Yo Y. Yamasaki; Takuya K. Hosoki; Hiyu Kanbe; Ryo Kakioka; Atsushi J. Nagano; Manabu Kume; Jun Kitano (Molecular Ecology, 2026)
Hybridization and introgression frequently occur even between distantly related species. A central question in speciation research is which genomic regions act as barriers to gene flow and how genome‐wide differentiation persists despite hybridization between species. Ecological divergence is well known to promote genomic differentiation, especially during the early stages of speciation. However, the extent to which ecological divergence contributes to genomic divergence and the restriction of gene flow between more strongly isolated species, such as those exhibiting intrinsic hybrid incompatibilities, remains relatively unclear. One promising approach is to compare genomic differentiation and introgression patterns between sympatric sites of ecologically divergent distantly related species and those of ecologically similar species. Here, we identified a new sympatric site of threespine stickleback ( Gasterosteus aculeatus ) and Japan Sea stickleback ( G. nipponicus ) in the Okinebe River, Hokkaido, Japan. In this habitat, these two species differ in migratory life histories: G. nipponicus is anadromous (sea‐run migratory), whereas G. aculeatus is resident. This contrasts with the other two previously studied sympatric sites, where both species are anadromous. We found that genomic differentiation in the Okinebe pair is maintained at high levels despite limited spatial isolation. Furthermore, the Okinebe pair had more genomic regions with high differentiation and fewer regions of introgression than the other sympatric pairs. These findings suggest that migratory differences may be able to contribute to the restriction of gene flow even between species with strong reproductive isolation. To better understand the role of ecological divergence in speciation, broader comparative studies across multiple sympatric species pairs with varying degrees of ecological differentiation and reproductive isolation are needed.

3D Genome Constrains Breakpoints of Inversions That Can Act as Barriers to Gene Flow in the Stickleback - Yo Y. Yamasaki; Atsushi Toyoda; Mitsutaka Kadota; Shigehiro Kuraku; Jun Kitano (Molecular Ecology, 2025)
DNA within the nucleus is organised into a well‐regulated three‐dimensional (3D) structure. However, how such 3D genome structures influence speciation processes remains largely elusive. Recent studies have shown that 3D genome structures influence mutation rates, including the occurrence of chromosomal rearrangement. For example, breakpoints of chromosomal rearrangements tend to be located at topologically associating domain (TAD) boundaries. Here, we hypothesised that TAD structures may constrain the location of chromosomal inversions and thereby shape the genomic landscape of divergence between species with ongoing gene flow, given that inversions can act as barriers to gene flow. To test this hypothesis, we used a pair of Japanese stickleback species, Gasterosteus nipponicus (Japan Sea stickleback) and G. aculeatus (three‐spined stickleback). We first constructed chromosome‐scale genome assemblies of both species using high fidelity long reads and high‐resolution proximity ligation data and identified several chromosomal inversions. Second, via population genomic analyses, we revealed higher genetic differentiation in inverted regions than in colinear regions and no gene flow within inversions, which contrasts with the significant gene flow in colinear regions. Third, using Hi‐C data, we revealed 3D genome structures of sticklebacks, delineated by A/B compartments and TADs. Finally, we found that inversion breakpoints tend to be located at TAD boundaries. Thus, our study demonstrates that the 3D genome constrains breakpoints of inversions that can act as barriers to gene flow in the stickleback. Further integration of 3D genome analyses with population genomics could provide novel insights into how the 3D genome influences speciation.

The genomics of discrete polymorphisms maintained by disruptive selection - Jun Kitano; Kotaro Kagawa; Takashi Tsuchimatsu; Ryo Yamaguchi; Masato Yamamichi (Trends in Ecology & Evolution, 2025)

Evolution of Size‐Fecundity Relationship in Medaka Fish From Different Latitudes - Shingo Fujimoto; Bayu K. A. Sumarto; Iki Murase; Daniel F. Mokodongan; Taijun Myosho; Mitsuharu Yagi; Satoshi Ansai; Jun Kitano; Satoshi Takeda; Kazunori Yamahira (Molecular Ecology, 2024)
In most fishes, the number of offspring increases with maternal body size. Although this size‐fecundity relationship often varies among species as a result of the coevolution of life‐history traits, the genetic basis of such size‐fecundity relationships remains unclear. We explored the genetic basis underlying this size‐fecundity relationship in two small medaka species, Oryzias latipes and O. sakaizumii . Our findings showed that O. sakaizumii has a higher fecundity than O. latipes , and quantitative trait locus analysis using interspecific F 2 hybrids showed that chromosome 23 is linked to the size‐fecundity relationship. In particular, the genes igf1 and lep‐b in this region are known to be associated with life‐history traits, including somatic growth, gonad maturation, and progeny numbers in various taxa. Because O. sakaizumii is distributed at higher latitudes and has a shorter spawning season than O. latipes in the wild, we propose that the relatively high fecundity observed in O. sakaizumii is an adaptation to high latitudes. We also discuss the potential ecological ramifications associated with the evolution of increased fecundity in this species.

Repositioning of centromere‐associated repeats during karyotype evolution in Oryzias fishes - Satoshi Ansai; Atsushi Toyoda; Kohta Yoshida; Jun Kitano (Molecular Ecology, 2024)
The karyotype, which is the number and shape of chromosomes, is a fundamental characteristic of all eukaryotes. Karyotypic changes play an important role in many aspects of evolutionary processes, including speciation. In organisms with monocentric chromosomes, it was previously thought that chromosome number changes were mainly caused by centric fusions and fissions, whereas chromosome shape changes, that is, changes in arm numbers, were mainly due to pericentric inversions. However, recent genomic and cytogenetic studies have revealed examples of alternative cases, such as tandem fusions and centromere repositioning, found in the karyotypic changes within and between species. Here, we employed comparative genomic approaches to investigate whether centromere repositioning occurred during karyotype evolution in medaka fishes. In the medaka family (Adrianichthyidae), the three phylogenetic groups differed substantially in their karyotypes. The Oryzias latipes species group has larger numbers of chromosome arms than the other groups, with most chromosomes being metacentric. The O. javanicus species group has similar numbers of chromosomes to the O. latipes species group, but smaller arm numbers, with most chromosomes being acrocentric. The O. celebensis species group has fewer chromosomes than the other two groups and several large metacentric chromosomes that were likely formed by chromosomal fusions. By comparing the genome assemblies of O. latipes , O. javanicus , and O. celebensis , we found that repositioning of centromere‐associated repeats might be more common than simple pericentric inversion. Our results demonstrated that centromere repositioning may play a more important role in karyotype evolution than previously appreciated.

The past, present, and a future for native charr in Japan - Kurt D. Fausch; Kentaro Morita; Jun-ichi Tsuboi; Yoichiro Kanno; Shoichiro Yamamoto; Daisuke Kishi; Jason B. Dunham; Itsuro Koizumi; Koh Hasegawa; Mikio Inoue; Takuya Sato; Satoshi Kitano (Ichthyological Research, 2024)
Charrs ( Salvelinus ) reach their southernmost distribution in Japan, and are uniquely adapted to the short, steep streams of this island archipelago. Southern Asian Dolly Varden ( Salvelinus curilus ) occur only in Hokkaido Island, whereas white-spotted charr ( Salvelinus leucomaenis ) range to southern Honshu. Both species diverged from an ancestral lineage during the late Pliocene/early Pleistocene, when lowered sea levels created semi-enclosed water bodies in the seas of Japan and Okhotsk. Genetic analyses showed S. curilus represents the most ancient divergence from the Dolly Varden ( Salvelinus malma ) - Arctic charr ( Salvelinus alpinus ) group, and revealed five lineages of S. leucomaenis which align differently than traditional subspecies. Japanese charr display diverse and flexible life histories including anadromous fish with partial migration, and fluvial, adfluvial, and resident forms. In Hokkaido, Dolly Varden are distributed upstream and white-spotted charr downstream. They coexist in narrow sympatric zones through adaptive shifts by Dolly Varden in behavior and morphology that facilitate benthic foraging. Both species hybridize with native and nonnative salmonids, and are displaced from microhabitats and decline in abundance when rainbow trout ( Oncorhynchus mykiss ) and brown trout ( Salmo trutta ) invade. Japan streams contain over 95,000 erosion control dams which create short stream fragments (medians ~200 m). This has increased extirpation of charr populations via lower genetic diversity and stochastic and demographic factors. Tributaries provide complex rearing habitats, afford refuges from floods, and supply recruits that sustain populations in mainstem fragments and create metapopulations in connected riverscapes. Charr play central roles in linked stream-riparian food webs, and cause direct and indirect effects that cascade to streambed algae and riparian predators when linkages are disrupted by anthropogenic effects or altered by native parasites. Many charr populations are threatened by habitat fragmentation and introgression or invasion by nonnative forms, but efforts to conserve charr are growing. These include restoring connectivity among pure populations above barriers that prevent invasions, protecting tributary nurseries, and instituting angling regulations to protect headwater populations. Key steps include inventorying pure populations, identifying conservation units, selecting appropriate management based on connectivity and biotic interactions, and engaging stakeholders and youth to engender an ethic for conserving irreplaceable charr lineages.

Multiple colonizations and hybridization of a freshwater fish group on a satellite island of Sulawesi - Ixchel F. Mandagi; Bayu K. A. Sumarto; Handung Nuryadi; Daniel F. Mokodongan; Sjamsu A. Lawelle; Kawilarang W.A. Masengi; Atsushi J. Nagano; Ryo Kakioka; Jun Kitano; Satoshi Ansai; Junko Kusumi; Kazunori Yamahira (Molecular Phylogenetics and Evolution, 2023)

Genetic basis for the evolution of pelvic‐fin brooding, a new mode of reproduction, in a Sulawesian fish - Javier Montenegro; Shingo Fujimoto; Satoshi Ansai; Atsushi J. Nagano; Masahiro Sato; Yusuke Maeda; Rieko Tanaka; Kawilarang W. A. Masengi; Ryosuke Kimura; Jun Kitano; Kazunori Yamahira (Molecular Ecology, 2022)
Modes of reproduction in animals are diverse, with different modes having evolved independently in multiple lineages across a variety of taxa. However, an understanding of the genomic change driving the transition between different modes of reproduction is limited. Several ricefishes (Adrianichthyidae) on the island of Sulawesi have a unique mode of reproduction called “pelvic‐fin brooding,” wherein females carry externally fertilized eggs until hatching using their pelvic fins. Phylogenomic analysis demonstrated pelvic‐fin brooders to have evolved at least twice in two distant clades of the Adrianichthyidae. We investigated the genetic architecture of the evolution of this unique mode of reproduction. Morphological analyses and laboratory observations revealed that females of pelvic‐fin brooders have longer pelvic fins and a deeper abdominal concavity, and that they can carry an egg clutch for longer than nonbrooding adrianichthyids, suggesting that these traits play important roles in this reproductive mode. Quantitative trait locus mapping using a cross between a pelvic‐fin brooder Oryzias eversi and a nonbrooding O. dopingdopingensis reveals different traits involved in pelvic‐fin brooding to be controlled by different loci on different chromosomes. Genomic analyses of admixture detected no signatures of introgression between two lineages with pelvic‐fin brooders, indicating that introgression is unlikely to be responsible for repeated evolution of pelvic‐fin brooding. These findings suggest that multiple independent mutations may have contributed to the convergent evolution of this novel mode of reproduction.

The evolutionary ecology of fatty‐acid variation: Implications for consumer adaptation and diversification - Cornelia W. Twining; Joey R. Bernhardt; Alison M. Derry; Cameron M. Hudson; Asano Ishikawa; Naoki Kabeya; Martin J. Kainz; Jun Kitano; Carmen Kowarik; Sarah Nemiah Ladd; Miguel C. Leal; Kristin Scharnweber; et al. (Ecology Letters, 2021)
The nutritional diversity of resources can affect the adaptive evolution of consumer metabolism and consumer diversification. The omega‐3 long‐chain polyunsaturated fatty acids eicosapentaenoic acid (EPA; 20:5n‐3) and docosahexaenoic acid (DHA; 22:6n‐3) have a high potential to affect consumer fitness, through their widespread effects on reproduction, growth and survival. However, few studies consider the evolution of fatty acid metabolism within an ecological context. In this review, we first document the extensive diversity in both primary producer and consumer fatty acid distributions amongst major ecosystems, between habitats and amongst species within habitats. We highlight some of the key nutritional contrasts that can shape behavioural and/or metabolic adaptation in consumers, discussing how consumers can evolve in response to the spatial, seasonal and community‐level variation of resource quality. We propose a hierarchical trait‐based approach for studying the evolution of consumers’ metabolic networks and review the evolutionary genetic mechanisms underpinning consumer adaptation to EPA and DHA distributions. In doing so, we consider how the metabolic traits of consumers are hierarchically structured, from cell membrane function to maternal investment, and have strongly environment‐dependent expression. Finally, we conclude with an outlook on how studying the metabolic adaptation of consumers within the context of nutritional landscapes can open up new opportunities for understanding evolutionary diversification.

Multiple paths to the same destination: Influence of gene flow on convergent evolution - Yo Y. Yamasaki; Jun Kitano (Molecular Ecology, 2021)
Elucidation of the genetic mechanisms of convergent evolution, the evolution of similar or the same phenotypes in phylogenetically independent lineages, helps predict how populations will respond to the same selective pressures. Convergent evolution can be caused by either the fixation of identical‐by‐descent alleles, independent mutations at the same gene, or mutations in different genes controlling the same trait. To what extent does the fixation of identical‐by‐descent alleles lead to convergent evolution in isolated populations where inflow of adaptive alleles from other populations is limited? In a From the Cover article in this issue of Molecular Ecology , Kemppainen et al. (2021) compared the genetic basis for the reduction of pelvic structures in three isolated freshwater populations of nine‐spined stickleback ( Pungitius pungitius ) from Northern Europe. The authors used quantitative trait loci (QTL) mapping to reveal that the pelvic reduction in these three populations was caused by mutations at different genetic loci. In contrast to studies in three‐spined stickleback ( Gasterosteus aculeatus ), where independently derived Pitx1 mutations were shown to be responsible for plate reduction across multiple freshwater populations, Kemppainen et al. (2021) found Pitx1 to be the candidate causative gene for only one population of P . pungitius . This study highlights the importance of genetic studies of convergent evolution, not only in the presence of gene flow but also in its absence for a better understanding of the genetic architecture of convergent evolution.

Functional divergence of a heterochromatin‐binding protein during stickleback speciation - Kohta Yoshida; Asano Ishikawa; Atsushi Toyoda; Shuji Shigenobu; Asao Fujiyama; Jun Kitano (Molecular Ecology, 2019)
Intragenomic conflict, the conflict of interest between different genomic regions within an individual, is proposed as a mechanism driving both the rapid evolution of heterochromatin‐related proteins and the establishment of intrinsic genomic incompatibility between species. Although molecular studies of laboratory model organisms have demonstrated the link between heterochromatin evolution and hybrid abnormalities, we know little about their link in natural systems. Previously, we showed that F 1 hybrids between the Japan Sea stickleback and the Pacific Ocean stickleback show hybrid male sterility and found a region responsible for hybrid male sterility on the X chromosome, but did not identify any candidate genes. In this study, we first screened for genes rapidly evolving under positive selection during the speciation of Japanese sticklebacks to find genes possibly involved in intragenomic conflict. We found that the region responsible for hybrid male sterility contains a rapidly evolving gene encoding a heterochromatin‐binding protein TRIM 24B. We conducted biochemical experiments and showed that the binding affinity of TRIM 24B to a heterochromatin mark found at centromeres and transposons, histone H4 lysine 20 trimethylation (H4K20me3), is reduced in the Japan Sea stickleback. In addition, mRNA expression levels of Trim24b were different between the Japan Sea and the Pacific Ocean testes. Further expression analysis of genes possibly in the TRIM 24B‐regulated pathway showed that some gypsy retrotransposons are overexpressed in the F 1 hybrid testes. We, therefore, demonstrate that a heterochromatin‐binding protein can evolve rapidly under positive selection and functionally diverge during stickleback speciation.

Genetic and stable isotope analyses of threespine stickleback from the Bering and Chukchi seas - Manabu Kume; Jun Kitano (Ichthyological Research, 2017)

Genetic basis for variation in salinity tolerance between stickleback ecotypes - Makoto Kusakabe; Asano Ishikawa; Mark Ravinet; Kohta Yoshida; Takashi Makino; Atsushi Toyoda; Asao Fujiyama; Jun Kitano (Molecular Ecology, 2017)
Adaptation to different salinities can drive and maintain divergence between populations of aquatic organisms. Anadromous and stream ecotypes of threespine stickleback ( Gasterosteus aculeatus ) are an excellent model to explore the genetic mechanisms underlying osmoregulation divergence. Using a parapatric pair of anadromous and stream stickleback ecotypes, we employed an integrated genomic approach to identify candidate genes important for adaptation to different salinity environments. Quantitative trait loci ( QTL ) mapping of plasma sodium concentrations under a seawater challenge experiment identified a significant QTL on chromosome 16. To identify candidate genes within this QTL , we first conducted RNA ‐seq and microarray analysis on gill tissue to find ecotypic differences in gene expression that were associated with plasma Na + levels. This resulted in the identification of ten candidate genes. Quantitative PCR analysis on gill tissue of additional Japanese stickleback populations revealed that the majority of the candidate genes showed parallel divergence in expression levels. Second, we conducted whole‐genome sequencing and found five genes that are predicted to have functionally important amino acid substitutions. Finally, we conducted genome scan analysis and found that eight of these candidate genes were located in genomic islands of high differentiation, suggesting that they may be under divergent selection. The candidate genes included those involved in ATP synthesis and hormonal signalling, whose expression or amino acid changes may underlie the variation in salinity tolerance. Further functional molecular analysis of these genes will reveal the causative genetic and genomic changes underlying divergent adaptation.

AcSKP1, a multiplex PCR-based co-dominant marker in complete linkage disequilibrium with the male-fertility restoration (Ms) locus, and its application in open-pollinated populations of onion - Yu Meng Huo; Bing Jiang Liu; Yan Yan Yang; Jun Miao; Li Min Gao; Su Ping Kong; Zhen Bao Wang; Hidemi Kitano; Xiong Wu (Euphytica, 2015)

Toward the genetic origins of a potentially non-native population of threespine stickleback (Gasterosteus aculeatus) in Alberta - Andrew M. Rezansoff; Erika Crispo; Christopher Blair; Edward Cruz; Jun Kitano; Steven M. Vamosi; Sean M. Rogers (Conservation Genetics, 2015)

Transcriptome analysis of predator‐ and prey‐induced phenotypic plasticity in the Hokkaido salamander ( Hynobius retardatus ) - Masatoshi Matsunami; Jun Kitano; Osamu Kishida; Hirofumi Michimae; Toru Miura; Kinya Nishimura (Molecular Ecology, 2015)
Predator‐ and prey‐induced phenotypic plasticity is widely observed among amphibian species. Although ecological factors inducing diverse phenotypic responses have been extensively characterized, we know little about the molecular bases of variation in phenotypic plasticity. Larvae of the Hokkaido salamander, Hynobius retardatus , exhibit two distinct morphs: the presence of their prey, Rana pirica tadpoles, induces a broad‐headed attack morph, and the presence of predatory dragonfly nymphs ( Aeshna nigroflava ) induces a defence morph with enlarged external gills and a high tail. To compare the genes involved in predator‐ and prey‐induced phenotypic plasticity, we carried out a de novo transcriptome analysis of Hokkaido salamander larvae exposed to either prey or predator individuals. First, we found that the number of genes involved in the expression of the defence morph was approximately five times the number involved in the expression of the attack morph. This result is consistent with the fact that the predator‐induced plasticity involves more drastic morphological changes than the prey‐induced plasticity. Second, we found that particular sets of genes were upregulated during the induction of both the attack and defence morphs, but others were specific to the expression of one or the other morph. Because both shared and unique molecular mechanisms were used in the expression of each morph, the evolution of a new plastic phenotype might involve both the co‐option of pre‐existing molecular mechanisms and the acquisition of novel regulatory mechanisms.

Ontogenetic stage‐specific quantitative trait loci contribute to divergence in developmental trajectories of sexually dimorphic fins between medaka populations - Maiko Kawajiri; Kohta Yoshida; Shingo Fujimoto; Daniel Frikli Mokodongan; Mark Ravinet; Mark Kirkpatrick; Kazunori Yamahira; Jun Kitano (Molecular Ecology, 2014)
Sexual dimorphism can evolve when males and females differ in phenotypic optima. Genetic constraints can, however, limit the evolution of sexual dimorphism. One possible constraint is derived from alleles expressed in both sexes. Because males and females share most of their genome, shared alleles with different fitness effects between sexes are faced with intralocus sexual conflict. Another potential constraint is derived from genetic correlations between developmental stages. Sexually dimorphic traits are often favoured at adult stages, but selected against as juvenile, so developmental decoupling of traits between ontogenetic stages may be necessary for the evolution of sexual dimorphism in adults. Resolving intralocus conflicts between sexes and ages is therefore a key to the evolution of age‐specific expression of sexual dimorphism. We investigated the genetic architecture of divergence in the ontogeny of sexual dimorphism between two populations of the Japanese medaka ( Oryzias latipes ) that differ in the magnitude of dimorphism in anal and dorsal fin length. Quantitative trait loci ( QTL ) mapping revealed that few QTL had consistent effects throughout ontogenetic stages and the majority of QTL change the sizes and directions of effects on fin growth rates during ontogeny. We also found that most QTL were sex‐specific, suggesting that intralocus sexual conflict is almost resolved. Our results indicate that sex‐ and age‐specific QTL enable the populations to achieve optimal developmental trajectories of sexually dimorphic traits in response to complex natural and sexual selection.

Identification of two SCAR markers co-segregated with the dominant Ms and recessive ms alleles in onion (Allium cepa L.) - Yan Yan Yang; Yu Meng Huo; Jun Miao; Bing Jiang Liu; Su Ping Kong; Li Min Gao; Chang Liu; Zhen Bao Wang; Yasuki Tahara; Hidemi Kitano; Xiong Wu (Euphytica, 2013)

Physiological and genetic basis for variation in migratory behavior in the three-spined stickleback, Gasterosteus aculeatus - Jun Kitano; Asano Ishikawa; Manabu Kume; Seiichi Mori (Ichthyological Research, 2012)
Closely related species of fish often exhibit different migration patterns. Even within species, anadromous and resident populations can be found in a diverse number of taxa. Although several environmental factors that regulate behavioral and physiological changes associated with fish migration have been identified, the genetic mechanisms underlying the variation in the ability to respond to these environmental cues in fishes that show different migratory behaviors are not well known. The three-spined stickleback Gasterosteus aculeatus (Linnaeus 1758) is a good model system for elucidation of the genetic basis for variation in migratory behaviors and other physiological changes associated with migration. First, the three-spined stickleback exhibits great inter-population variation in migration patterns. Second, genetic and genomic tools are now available for studying this species. In the present study, variation in the migration patterns among G. aculeatus populations and the recent progress in our understanding of the genetic and physiological basis for variation in traits important for G. aculeatus migration are reviewed.

Turnover of sex chromosomes and speciation in fishes - Jun Kitano; Catherine L. Peichel (Environmental Biology of Fishes, 2012)

A large-scale collection of phenotypic data describing an insertional mutant population to facilitate functional analysis of rice genes - Akio Miyao; Yukimoto Iwasaki; Hidemi Kitano; Jun-Ichi Itoh; Masahiko Maekawa; Kazumasa Murata; Osamu Yatou; Yasuo Nagato; Hirohiko Hirochika (Plant Molecular Biology, 2007)